2011
DOI: 10.1016/j.exppara.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei: Two mitogen activated protein kinase kinases are dispensable for growth and virulence of the bloodstream form

Abstract: Mitogen activated protein kinase cascades function in eukaryotic responses to the environment and stress. Trypanosomatid parasites possess protein kinases with sequences characteristic of kinases in such cascades. In this report we use gene knockouts to demonstrate that two mitogen activated kinase kinase genes, MKK1 (Tb927.3.4860) and MKK5 (Tb927.10.5270), are not essential in the pathogenic bloodstream stage of Trypanosoma brucei, either in vitro or in vivo. Bloodstream forms lacking MKK1 showed decreased gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…1A). As previously reported for null mutants of MKK1 in monomorphic bloodstream forms [14], there was no growth defect ( Fig. 1B), nor were there discernable alterations to the flagellum (data not shown).…”
supporting
confidence: 67%
See 3 more Smart Citations
“…1A). As previously reported for null mutants of MKK1 in monomorphic bloodstream forms [14], there was no growth defect ( Fig. 1B), nor were there discernable alterations to the flagellum (data not shown).…”
supporting
confidence: 67%
“…Recently, null mutants of two T. brucei MKKs, MKK1 and MKK5, were described [14]. Neither gene was essential for slender bloodstream forms, but the MKK1 null mutant was slightly more sensitive than its wild-type parent to being cultured at 39 • C. In contrast to its Leishmania orthologue, T. brucei MKK1 did not play a significant role in flagellar biogenesis.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The knockout of these genes in bloodstream forms did not cause changes in cell growth in standard culture conditions; however, defects in proliferation were observed upon exposure to temperature stress 13 . Interestingly, in the same work, western blot analysis suggested that MKK5 expression is higher in the procyclic than in the bloodstream forms of T. brucei 13 , which may indicate that the role of this protein is developmental stage-specific. To date, the function of MKK5 in procyclic forms of T. brucei has not yet been addressed.…”
Section: Introductionmentioning
confidence: 91%